PERBANDINGAN KINERJA ALGORITMA NAÏVE BAYES DAN C4.5 UNTUK MENDETEKSI PENGELABUAN UNIFORM RESOURCE LOCATOR (PHISHING URL) - Kevin Marcello Jonathan; Bagus Mulyawan; Novario Jaya Perdana (Jurnal Ilmu Komputer dan Sistem Informasi, 2020)
Nowadays, phone or smartphone and internet are something that cannot be separated with human. One of negative effects of using internet is cyber crime like a phishing url. Phishing url is usually used to collecting personal information like pin number, credit card etc. There are many type of classification algorithm, two of them is Naïve Bayes and C4.5. Both of the alogithm is good for recognizing a phishing url. This website created are used to classify a unkown url with Naïve Bayes and C4.5 algorithm. The accuracy of C4.5 algorithm is 87.11% and 78.48% for Naïve Bayes. The average time needed to processing one url is 21.78 second for C4.5 and 23.31 second for Naïve Bayes.